Determinants of smallholder farmers’ participation in rice value chains in Uganda - Rugema, S.H.; Sseguya, H.; Kibwika, P. (African Journals Online, 2018)
This study explored the key determinants of smallholder farmers’ participation in the One Stop Centre Farmer Association (OSCA) rice value chains in Uganda. Data were collected from 98 respondents in Luwero and Bugiri districts using focus group discussions and 20 key informant interviews, and analysed with NVIVO software. The findings indicated that style of leadership, trust, cohesive networks and support services were key determinants of participation. Minimal participation of some members occurred due to unrealistic expectations and incompetent leadership. Further, addressing OSCA objectives can mitigate ensuing expectations. Along with this, strengthening the OSCA leadership to entrench transparency and establishment of business models for integration of value chain interventions into the wider livelihood strategies is important in order to cater for interests of all the members.